2021
DOI: 10.1111/ejn.15166
|View full text |Cite
|
Sign up to set email alerts
|

Low pre‐stimulus EEG alpha power amplifies visual awareness but not visual sensitivity

Abstract: Pre‐stimulus oscillatory neural activity has been linked to the level of awareness of sensory stimuli. More specifically, the power of low‐frequency oscillations (primarily in the alpha‐band, i.e., 8–14 Hz) prior to stimulus onset is inversely related to measures of subjective performance in visual tasks, such as confidence and visual awareness. Intriguingly, the same EEG signature does not seem to influence objective measures of task performance (i.e., accuracy). We here examined whether this dissociation hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
51
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 78 publications
9
51
5
Order By: Relevance
“…Our regression analysis showed, in addition to the effect of lateralization on contrast appearance, and the effect of bilateral pre-stimulus alpha amplitude on objective accuracy in the contrast judgment task: stronger amplitude was related to worse performance. This result was unexpected because it conflicts with recent studies showing that pre-stimulus alpha amplitude affects criterion, not accuracy in visual detection tasks (Limbach and Corballis, 2016; Iemi et al, 2017; Iemi and Busch, 2018), and does not affect performance in discrimination tasks (Samaha et al, 2017; Benwell et al, 2017; Samaha et al, 2020b; Benwell et al, 2021). Given that states of high alpha amplitude indicate low arousal (Johnston et al, 2020), diminishing the quality of stimulus representations (Zhou et al, 2021), one possibility is that the effect we observed was merely a by-product of fatigue, which in turn caused the effect on accuracy.…”
Section: Discussioncontrasting
confidence: 99%
“…Our regression analysis showed, in addition to the effect of lateralization on contrast appearance, and the effect of bilateral pre-stimulus alpha amplitude on objective accuracy in the contrast judgment task: stronger amplitude was related to worse performance. This result was unexpected because it conflicts with recent studies showing that pre-stimulus alpha amplitude affects criterion, not accuracy in visual detection tasks (Limbach and Corballis, 2016; Iemi et al, 2017; Iemi and Busch, 2018), and does not affect performance in discrimination tasks (Samaha et al, 2017; Benwell et al, 2017; Samaha et al, 2020b; Benwell et al, 2021). Given that states of high alpha amplitude indicate low arousal (Johnston et al, 2020), diminishing the quality of stimulus representations (Zhou et al, 2021), one possibility is that the effect we observed was merely a by-product of fatigue, which in turn caused the effect on accuracy.…”
Section: Discussioncontrasting
confidence: 99%
“…Here, we recorded electro-encephalography (EEG) during visual search tasks with varying attentional load to test the link between brain oscillations and task demands, and further characterize periodic attentional sampling. We first replicated previous results showing that prestimulus phase [20,[31][32][33][34][35][36][37][38][39][40] and post-stimulus phase-locking across trials [20,41] of low-frequency oscillations predict successful task performance (same task as in [20]). Specifically, the phase of spontaneous oscillations (before stimuli onset) predicts trial outcome; and post-stimulus phase alignment (phase-locking) aids performance, which we call phase reset here to refer, strictly, to the mathematical description of the effect [42].…”
Section: Introductionsupporting
confidence: 83%
“…The assumption of additive pre-post-stimulus interaction stands counter to various fMRI studies [ 69 , 70 , 71 ] and EEG/MEG [ 55 , 72 , 73 , 74 , 75 , 76 ] that show the importance of pre-stimulus activity changes for conscious contents (see also [ 77 ]).…”
Section: Neuronal Mechanisms—from Pre-stimulus To Stimulus-induced Ac...mentioning
confidence: 94%